2017
DOI: 10.18632/aging.101178
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the influence of age on GABAA and glutamatergic mediated functions in the dorsolateral prefrontal cortex using paired-pulse TMS-EEG

Abstract: Gamma-aminobutyric acid (GABA)ergic and glutamatergic neurotransmissions in the prefrontal cortex decreases with age. Further, cognitive function mediated through the dorsolateral prefrontal cortex (DLPFC) also declines with age. Although neuroimaging studies have demonstrated decreased levels of these substances, direct neurophysiological data investigating the effect of aging in the DLPFC in human subjects is lacking. The advent of transcranial magnetic stimulation (TMS) combined with electroencephalography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…Previous research has demonstrated relationship between P60 and N100 (Noda, Zomorrodi, Cash, et al, 2017d). We explored whether there was an association in changes in the amplitude of these peaks following iTBS.…”
Section: Effects Of Itbs On the Relationship Between P60 And N100mentioning
confidence: 94%
See 4 more Smart Citations
“…Previous research has demonstrated relationship between P60 and N100 (Noda, Zomorrodi, Cash, et al, 2017d). We explored whether there was an association in changes in the amplitude of these peaks following iTBS.…”
Section: Effects Of Itbs On the Relationship Between P60 And N100mentioning
confidence: 94%
“…While it is speculative, the correlations between working memory performance and the ratio of P60 and N100 may partially be explained by the well-maintained modulation of potential inhibition (N100) and excitation (P60) (Noda, Zomorrodi, Cash, et al, 2017d). While it is speculative, the correlations between working memory performance and the ratio of P60 and N100 may partially be explained by the well-maintained modulation of potential inhibition (N100) and excitation (P60) (Noda, Zomorrodi, Cash, et al, 2017d).…”
Section: Relationship Between Neurophysiological Changes and The Chmentioning
confidence: 99%
See 3 more Smart Citations